Commentary and Correspondence - Thompson, W. Scott; Martin, Phillip W.D. (Tufts Archival Research Center, 2005)
Volume 5, Issue 2. Summer. Rhetoric and Reality. The "Hostage Crisis". Commentary and Correspondence